Development and Validation of a Method for the Analysis of Multiple Pesticides in Fishery Products Using Gas Chromatography with Micro-Electron Capture Detection and Gas Chromatography–Tandem Mass Spectrometry - Myungheon Kim; Mihyun Cho; Changkyo Seo; Jaebin Im; Changhyeon Park; Yoonmi Lee; Mi-Ra Jo; Yong-Sun Moon; Moo-Hyeog Im (Separations)
This study aims to develop a simultaneous analytical method for detecting 19 pesticides, including 4,4′-DDD, in fishery products using gas chromatography with micro-electron capture detection (GC-μECD) and gas chromatography–tandem mass spectrometry (GC-MS/MS). A new analytical method was developed to measure pesticide residues in fishery products based on the modified Association of Official Analytical Chemists protocol combining quick, easy, cheap, effective, rugged, and safe (QuEChERS) and the Pesticide Analytical Manual for extraction and purification. Extraction was performed using acetonitrile containing 0.1% acetic acid, and purification was conducted with Florisil cartridges. The Florisil cartridges were more effective than QuEChERS in removing impurities and pigments during purification and also resulted in a reduced matrix effect. The validation followed Codex guidelines (CAC/GL 40). The limit of detection ranged from 2 to 3 ng/g, and the limit of quantification (LOQ) from 7 to 10 ng/g. Matrix-matched calibration curves exhibited linearity with coefficients of determination exceeding 0.99 for all target analytes. Accuracy was assessed based on recovery rates, while precision was evaluated using relative standard deviations (RSD) at three spiking levels (LOQ, 10×LOQ, and 50×LOQ). The recovery rates ranged from 62.6 to 119.1%, with RSDs of 0.4 to 19.5%, conforming to Codex guidelines.